Oligodendroglia are particularly vulnerable to oxidative damage after neurotrauma in vivo - Giacci, M.; Bartlett, Carole; Smith, N.; Iyer, K.; Toomey, Lillian; Jiang, H.; Guagliardo, P.; Kilburn, M.; Fitzgerald, Melinda (Society for Neuroscience, 2018)
Loss of function following injury to the central nervous system is worsened by secondary degeneration of neurons and glia surrounding the injury and initiated by oxidative damage. However, it is not yet known which cellular populations and structures are most vulnerable to oxidative damage in vivo Using Nanoscale secondary ion mass spectrometry (NanoSIMS), oxidative damage was semi-quantified within cellular subpopulations and structures of optic nerve vulnerable to secondary degeneration, following a partial transection of the optic nerve in adult female PVG rats. Simultaneous assessment of cellular subpopulations and structures revealed oligodendroglia as the most vulnerable to DNA oxidation following injury. 5-ethynyl-2'-deoxyuridine (EdU) was used to label cells that proliferated in the first 3 days after injury. Injury led to increases in DNA, protein and lipid damage in OPCs and mature oligodendrocytes at 3 days, regardless of proliferative state, associated with a decline in the numbers of OPCs at 7 days. O4+ pre-oligodendrocytes also exhibited increased lipid peroxidation. Interestingly, EdU+ mature oligodendrocytes derived after injury demonstrated increased early susceptibility to DNA damage and lipid peroxidation. However, EdU- mature oligodendrocytes with high 8OHdG immunoreactivity were more likely to be caspase3+. By day 28, newly derived mature oligodendrocytes had significantly reduced MYRF mRNA indicating that the myelination potential of these cells may be reduced. The proportion of caspase3+ oligodendrocytes remained higher in EdU- cells. Innovative use of NanoSIMS together with traditional immunohistochemistry and in situ hybridisation have enabled the first demonstration of subpopulation specific oligodendroglial vulnerability to oxidative damage, due to secondary degeneration in vivo. SIGNIFICANCE STATEMENT. Injury to the central nervous system is characterised by oxidative damage in areas adjacent to the injury. However, the cellular subpopulations and structures most vulnerable to this damage remain to be elucidated. Here we use powerful NanoSIMS techniques to show increased oxidative damage in oligodendroglia and axons and to demonstrate that cells early in the oligodendroglial lineage are the most vulnerable to DNA oxidation. Further immunohistochemical and in situ hybridisation investigation reveals that mature oligodendrocytes derived after injury are more vulnerable to oxidative damage than their counterparts existing at the time of injury and have reduced MYRF mRNA, yet pre-existing oligodendrocytes are more likely to die.